Оrganometric changes in thymus under the influence of propylene glycol - Shyian, D.; Avilova, Olga; Bondareva, A.; Prykhodko, O. (Тбилисский государственный медицинский университет, 2019)
The scientific interest in the influence of xenobiotics on the human body is due to the fact that immune organs are character¬ized by a pronounced response to the influence of endogenous and exogenous factors. Recently, the immunological impair¬ment, as a manifestation of reactions to ecopathogenic condi¬tions, suggests a major pathogenesis role in the development of cardiovascular, neuropsychiatric diseases, as well as diffuse diseases of connective tissue. Objectives - experiment was designed to elucidate the organo¬metric changes in thymus of male rats due to impact of propyl¬ene glycol. 40 WAG matured male rats were divided randomly into two groups. The first group served as a control and constituted 8 animals. The sec¬ond group of 32 rats, 8 rodents in each, were treated via gavage by aqueous solutions of propylene glycol in doze 1/10 LD50 in conversion to 26,38 g/kg during 7, 15, 30, 45 days. All animals were sacrificed on the term defined by experimental design. Thymus specimens were dis¬sected out, and linear dimensions (length, width, height) using digital caliper were measured, along with mass and volume of the thymus. Limits of the thymus morphometric indices’ variability in intact and experimental groups were calculated. The research indicates that exposure to propylene glycol caused marked organometric changes in rats’ thymus. However, more pro¬nounced changes were observed on 7th and 30th days. Were estab¬lished the following limits of variability indices oscillations: IndHL of the experimental group thymus ranged from min=12.57 to max=47.54, the mean value was from 24.67 to 28.02; IndHW of the experimental group thymus ranged from min=11.96 to max=88.73, the mean value was from 36.78 to 41.41; IndT of the experimental group ranged from min = 38.17 to max=141.3, the mean value was from 71.1 to 86.52. The study of the morphometric parameters of the thymus in the experimental group of rats has established a sig¬nificant reduction of all parameters and their deviation from the pa¬rameters of the control group, that shows active reaction of thymus on induced xenobiotic.
Keywords: thymus; rats; xenobiotics; organometry; propylene glycol